Anti-SARS-CoV-2 T-stem cell memory persists in ocrelizumab-treated MS patients. (October 2022) - Guerrera, Gisella; Mandelli, Alessandra; Finardi, Annamaria; Orrico, Mario; D'Orso, Silvia; Picozza, Mario; Noviello, Maddalena; Beretta, Valeria; Bonetti, Bruno; Calabrese, Massimiliano; Marastoni, Damiano; De Rossi, Nicola; et al.
Background: Development of long-lasting anti-severe acute respiratory syndrome coronavirus 2 (SARS-CoV2) T-cell responses in persons with multiple sclerosis (pwMS) treated with ocrelizumab is questioned. Objective: Investigate antiviral T-cell responses after infection with SARS-CoV-2 in ocrelizumab-treated pwMS. Control groups included ocrelizumab-treated pwMS without SARS-CoV-2 infection, and non-MS individuals with and without SARS-CoV-2 infection. Methods: Peripheral blood mononuclear cells were stimulated with SARS-CoV-2 peptide pools and T-cell reactivity was assessed by ELISPOT for interferon (IFN)-γ detection, and by multiparametric fluorescence-activated cell sorting (FACS) analyses for assessment and characterization of T-cell activation. Results: ELISPOT assay against the spike and the N protein of SARS-CoV-2 displayed specific T-cell reactivity in 28/29 (96%) pwMS treated with ocrelizumab and infected by SARS-CoV-2, similar to infected persons without MS. This reactivity was present 1 year after infection and independent from the time of ocrelizumab infusion. FACS analysis following stimulation with SARS-CoV-2 peptide pools showed the presence of activation-induced markers (AIMs) in both CD4 + and CD8 + T-cell subsets in 96% and 92% of these individuals, respectively. Within naïve AIM + CD4 + and CD8 + T-cells, we detected T memory stem cells, suggesting the acquisition of long-term memory. Conclusions: B-cell depletion using ocrelizumab does not impair the development of long-lasting anti-SARS-CoV-2 T-cell responses.